2022
DOI: 10.3390/cancers14246261
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Clinical and CT-Based Radiomic Features for Pretreatment Prediction of Pathologic Complete Response to Neoadjuvant Systemic Therapy in Breast Cancer

Abstract: The purpose of the present study was to examine the potential of a machine learning model with integrated clinical and CT-based radiomics features in predicting pathologic complete response (pCR) to neoadjuvant systemic therapy (NST) in breast cancer. Contrast-enhanced CT was performed in 329 patients with breast tumors (n = 331) before NST. Pyradiomics was used for feature extraction, and 107 features of seven classes were extracted. Feature selection was performed on the basis of the intraclass correlation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Tsai et al. ( 27 ) established a model based on the radiomic features and clinical features of CT, and all 6 clinical features were used in the construction of the clinical model. The final AUC was 0.69, showing moderate performance, while the AUCs of our clinical model were 0.864 and 0.781, showing better efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsai et al. ( 27 ) established a model based on the radiomic features and clinical features of CT, and all 6 clinical features were used in the construction of the clinical model. The final AUC was 0.69, showing moderate performance, while the AUCs of our clinical model were 0.864 and 0.781, showing better efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the number of selected predictors after univariate analysis and multifactor analysis is small, unable to reflect most clinical information of patients, and has little clinical adaptability, we intended to incorporate all eight clinical factors into the model construction. Tsai et al (27) established a model based on the radiomic features and clinical features of CT, and all 6 clinical features were used in the construction of the clinical model. The final AUC was 0.69, showing moderate performance, while the AUCs of our clinical model were 0.864 and 0.781, showing better efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…(2) The significant variables identified in the multivariate analysis were consistent with previous studies. Fourth, it is worth noting that manual tumor segmentation for radiomics analysis is time-consuming and labor-intensive (Tsai et al 2022 ), which may limit its clinical usefulness. Finally, since radiomics features are potentially dependent on imaging quality and incorporating clinical and radiomic signature into one nomogram might reduce the robustness of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Six of the 10 features extracted in the present study belong to spatial gray level co-occurrence matrix (GLCM) features. Previous studies have shown that GLCM features are helpful in the pretreatment prediction of pathological complete response to no special type(NST) in breast cancer [ 27 ]. GLSZM texture features have been useful in differentiating between two different tumors in studies using CT imaging omics to distinguish between pelvic rhabdomyosarcoma and yolk cystoma in children [ 28 ].…”
Section: Discussionmentioning
confidence: 99%